Red queen [large type] - Gómez-Jurado, Juan (Gómez-Jurado, Juan. Antonia Scott trilogy, 2023)
"Antonia Scott--the daughter of a British diplomat and a Spanish mother--has a gifted forensic mind, whose ability to reconstruct crimes and solve baffling murders is legendary. But after a personal trauma, she's refused to continue her work or even leave her apartment. Jon Gutierrez, a police officer in Bilbao--disgraced, suspended, and about to face criminal charges--is offered a chance to salvage his career by a secretive organization that works in the shadows to direct criminal investigations of a highly sensitive nature. All he has to do is succeed where many others have failed: Convince a recalcitrant Antonia to come out of her self-imposed retirement, protecting her and helping her investigate a new, terrifying case. The case is a macabre, ritualistic murder--a teen-aged boy from a wealthy family whose body was found without a drop of blood left in it. But the murder is just the start. A high-ranking executive and daughter of one of the richest men in Spain is kidnapped, a crime which is tied to the previous murder. Behind them both is a hidden mastermind with even more sinister plans. And the only person with a chance to see the connections, solve the crimes and successfully match wits with the killer before tragedy strikes again...is Antonia Scott" --